Petroleum generation kinetics of unconventional Mississippian mudrocks in central Oklahoma, United States - Atwah, Ibrahim; Sweet, Stephen (Frontiers in Earth Science, 2023)
The Mississippian mudrocks of central Oklahoma, USA, encompass hydrocarbon-rich unconventional reservoirs. Many factors control the success of hydrocarbon producibility from the Sooner Trend oilfield, Anadarko Basin, and Canadian and Kingfisher Counties (‘STACK’) play in Oklahoma, including rock mineralogy, thermal maturity, and organic richness. Petroleum sourcing in these Mississippian reservoirs is complex, encompassing multiple hydrocarbon charges from different source rocks in addition to the Woodford Shale. Therefore, determining petroleum generation kinetic parameters for Mississippian mudrocks is crucial to understand the thermal maturation and associated hydrocarbon fluid types, which can ultimately aid in identifying the ‘sweet spot’. This investigation presents the first experimental evidence of petroleum generation kinetics for the Mississippian mudrocks in central Oklahoma. Here, core samples collected from Lincoln County, central Oklahoma, were examined for petroleum generation kinetics using a hydrous pyrolysis reactor. Generated pyrolysate products were then examined for key molecular parameters in comparison with produced crude oils. The results from the hydrous pyrolysis experiments and corresponding Arrhenius plots suggest slightly higher reaction rates for hydrocarbons generated from the Mississippian mudrocks. These reaction rates result in lower activation energy and frequency factor values for the Mississippian mudrocks when compared to the Woodford Shale. Molecular signatures from pyrolysate oils match with Mississippian sourced crude oils with a predominance of lower and extended tricyclic terpane biomarkers. The geological implications of the determined kinetics suggest that Mississippian petroleum source rocks can generate oil and gas at lower temperatures compared to the Woodford Shale. The low kinetic parameters of Mississippian rocks are postulated due to organic-matter structure co-occurring as infused amorphinite and bituminite within the mineral matrix. The large surface area between the macerals and the mineral matrix could increase the reactivity, with clays acting as catalysts for petroleum generation.